g ????? ?????? ?????? ??????? ?? ???? ??????? ???????? ???????? ?????? ?????? ???????? (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
In this study , the adsorption of an industrial blue dye was investigated by using date palm tree waste . The effect of the process parameters such as, contact time ; adsorbate concentration, ( pH) and (temperature ) are reported . "Nearly 2-3 hr of contact time are found to be sufficient for the adsorption to reach equilibrium" (A better fixation was obtained at acidic pH (2) and room temperature 25?C.